'No regionalism please, we are Leghisti !' The transformation of the Italian Lega Nord under the leadership of Matteo Salvini. Issue 5 (20th October 2018) - Albertazzi, Daniele; Giovannini, Arianna; Seddone, Antonella
ABSTRACT: Whilst the Lega Nord has traditionally been defined as a regionalist populist party, since Matteo Salvini became its leader in 2013 it has undergone a process of profound ideological transformation. This article assesses this momentous change and the impact it could have on the future of the Lega, drawing on a content analysis of Salvini's and the party's Facebook posts, as well as interviews with regional leaders. It argues that, under Salvini's personal style of leadership: (a) regionalism has been replaced by an empty form of nativist nationalism, which fails to address socio-economic issues related to the North–South divide; (b) populism remains central to the party's strategic communication, but the EU has taken Rome's place as the people's 'enemy'; (c) this ideological shift has paid-off at the 2018 general election, but is underpinned by latent fractures between the leader and regional representatives which could have profound implications in the future.